2004
DOI: 10.1001/archotol.130.6.732
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Sox9 in Patterning Tracheal Cartilage Ring Formation in an Embryonic Mouse Model

Abstract: To identify genes expressed early in the formation of the mouse trachea that control patterning of tracheal cartilaginous rings. Design: The mouse larynx and trachea begin as an outpouching from the ventral foregut endoderm at embryonic day (E) 9. Digoxigenin-labeled RNA probes to putative tracheal patterning genes were generated by in vitro transcription. Embryos ranging in age from E9 to E16 were then subjected to whole-mount in situ hybridization using these labeled RNA probes. The RNA probes were then loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…4 H). Col2a1 is a direct target of Sox9 and it is expressed in developing trachea at E10.5 in a similar distribution to that of Sox9 (Elluru et al, 2009; Elluru and Whitsett, 2004). We utilized Col2a1Cre mice to delete Sox9 in chondrocyte progenitors.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…4 H). Col2a1 is a direct target of Sox9 and it is expressed in developing trachea at E10.5 in a similar distribution to that of Sox9 (Elluru et al, 2009; Elluru and Whitsett, 2004). We utilized Col2a1Cre mice to delete Sox9 in chondrocyte progenitors.…”
Section: Resultsmentioning
confidence: 95%
“…Mesenchymal cells derived from the splanchnic mesoderm, positioned ventral to the developing tracheal tube express the transcription factor Sox9 as early as E9 (Elluru and Whitsett, 2004; Hines et al, 2013). Sox9 is a key regulator of cartilage and bone development (Akiyama, 2008; Akiyama et al, 2002) and its role in tracheal cartilage has been demonstrated (Arora et al, 2012; Elluru and Whitsett, 2004; Hines et al, 2013; Park et al, 2010; Turcatel et al, 2013). Signaling mechanisms controlling the initial specification of tracheal cartilage progenitors are poorly defined; however, a number of transcription factors, receptors and ligands that influence Sox9 expression in the mesenchyme of the trachea have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…However, Sox9 is also expressed in the proximal mesenchyme, specifically in the precursor and differentiated cartilages of both the trachea and main bronchi (Elluru et al 2004). As Sox9 is a key gene essential for cartilage development (Bi et al 2001), it likely plays a role in airway cartilage ring formation.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal expression of SHH has been associated with glossoptosis, pyriform aperture stenosis, tracheoesophageal fistula, and/or laryngotracheoesophageal cleft malformations (25). Multiple other cytokines and transcription factors have been implicated in upper airway anomalies (Table 3) (26)(27)(28)(29)(30)(31)(32)(33)(34). It is likely that other mouse models display upper airway abnormalities that have not been identified due to lack of screening by investigators with appropriate knowledge.…”
Section: Priority Area 2: Creation Of Animal Models To Aid In the Undmentioning
confidence: 99%